The Social Studies Educators in the Philippine Licensure Examination for Teachers: Challenges and Implications - Francis Edward A. Blanco (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study explores the unique challenges faced by Social Studies educators from a state university in Central Luzon, Philippines, in passing the Licensure Examination for Teachers (LET) and aims to provide implications for enhancing preparation strategies and improving overall passing rates. Methodology: This study utilized a descriptive qualitative methodology, employing in-depth interviews, analytical memos, and self-reflective journals as data collection tools. Data analysis was conducted using Bingham and Witkowsky’s (2023) Five-Phase Process of Qualitative Data Analysis with the aid of a software for qualitative data analysis. Data credibility was ensured through cross-verification. Main Findings: Social Studies educators struggled with poor time management and job priorities which led to limited preparation time while inadequate rest and exam policy awareness contributed to poor performance. The struggles contributed to unfavorable outcomes in the initial attempts at passing the LET. Novelty/Originality of this study: Existing research highlights the importance of passing the LET for career advancement and teaching quality, yet few studies examine the challenges affecting Social Studies educators. Addressing the gap, this study provides a deeper understanding of the challenges these educators face offering implications to improve LET preparation strategies and contribute to teacher certification research and professional development.